Distribusi Konsentrasi COD dan TSS pada Pengolahan Limbah Tahu dengan menggunakan Reaktor Alir Pipa - Sitti Sahreni; Harjanto Harjanto; Mustafa Mustafa; Musdalifah Musdalifah; Firman Firman (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Liquid waste in tofu industry has the COD and TSS values that exceed the environmental quality standards.The high value of COD and TSS liquid waste in tofu industry is caused by the high organic level.The organic content from tofu industry can be lowered by a fermentation process using a reactor.This study is conducted to investigate the effect of the reactor’s length to the decreasing level of COD and TSS liquid waste of tofu industry with fermentation method using cow intestines as starter.This research was conducted by varying the sampling length of the reactor’s flow pipe from 20 cm, 40 cm, 60 cm, and 80 cm.The process was done within 45 days and a loading rate of 0.8 L/5 days.Based on the results of the research, time and sampling length affect the % of the decreasing level of COD and TSS.The fermentation process using flow pipe reactor enables the COD to get lower, up to 98.57% with the COD value of 196 mg/L at 80 cm sampling length on day 45, while the TSS can be lowered up to 77.38% with TSS value of 38 mg/L at 80 cm sampling length on day 45. The values of COD and TSS have met the environmental quality standards based on the number 02 of2011 East Kalimantan provincial.